2019
DOI: 10.1371/journal.pone.0226401
|View full text |Cite
|
Sign up to set email alerts
|

“That’s all Fake”: Health professionals stigma and physical healthcare of people living with Serious Mental Illness

Abstract: Background People living with a Serious Mental Illness (SMI) die earlier than the general population due to preventable medical conditions. Latinos living with SMI are a particularly vulnerable population with higher prevalence of chronic medical conditions. Stigma has been identified as a factor that fosters health inequities for Latinos/as with SMI, particularly Puerto Ricans. Although personal and social consequences of stigmatization have been well documented, research regarding the role of cultural factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0
11

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 84 publications
2
37
0
11
Order By: Relevance
“…27 Other recent studies have highlighted the role of cultural and family stigma as important barriers to mental health services among Latinos, the benefits of provider concordance among Latinos in terms of patient satisfaction and engagement in care, and the potential role of peer navigators to better support Latinos with SMI accessing both mental and physical health services. [49][50][51]…”
Section: Discussionmentioning
confidence: 99%
“…27 Other recent studies have highlighted the role of cultural and family stigma as important barriers to mental health services among Latinos, the benefits of provider concordance among Latinos in terms of patient satisfaction and engagement in care, and the potential role of peer navigators to better support Latinos with SMI accessing both mental and physical health services. [49][50][51]…”
Section: Discussionmentioning
confidence: 99%
“…Hiring of minority peer specialists may reflect greater cultural sensitivity/competency within the program, and/or minority peer staff may contribute to a culturally sensitive climate (Jones et al 2020 ). Racial/ethnic concordance between peers and youth may play a positive role by increasing client trust and rapport (Corrigan et al 2018 ; Corrigan et al 2017a , b ), or by helping youth manage family and/or community stigma regarding mental illness (Greden et al 2010 ; Rivera-Segarra et al 2019 ). These possible interpretations all merit further exploration, including qualitative interviews designed to help unpack underlying directionality, processes and mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…These negative attitudes can compromise somatic healthcare professionals' ability to respond to medical symptoms and deliver qualitative somatic care (29). Interestingly, several studies (31)(32)(33) have demonstrated that even mental healthcare professionals have negative stereotypes and social distance desire towards people with SMI, particularly people with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%